Mixed Initial Boundary-value Problem for Some Multidimensional Nonlinear Schrodinger Equations Including Damping (Journal of Partial Differential Equations, 1992)
The motivation of this paper is the study of the unique existence of weak and smooth solutions for the mixed initial boundary-value problem of some multidimensional nonlinear Schr&#246dinger equations induding damping.
Keywords: Global solutions; nonlinear Schr&#246dinger equations; Galerkin method